Genome-Wide Screening, Cloning, Chromosomal Assignment, and Expression of Full-Length Human Endogenous Retrovirus Type K - Tönjes, Ralf R. (American Society for Microbiology, 1999)
The human genome harbors 25 to 50 proviral copies of the endogenous retrovirus type K (HERV-K), some of which code for the characteristic retroviral proteins Gag, Pol, and Env. For a genome-wide cloning approach of full-length and intact HERV-K proviruses, a human P1 gene library was screened with a gag-specific probe. Both HERV-K type 1 and 2 clones were isolated. Sixteen HERV-K type 2 proviral genomes were characterized by direct coupled in vitro transcription-in vitro translation assays to analyze the coding potential of isolated gag, pol, and env amplicons from individual P1 clones. After determination of long terminal repeat (LTR) sequences and adjacent chromosomal integration sites by inverse PCR techniques, two HERV-K type 2 proviruses displaying long retroviral open reading frames (ORFs) were assigned to chromosomes 7 (C7) and 19 (C19) by using a human-rodent monochromosomal cell hybrid mapping panel. HERV-K(C7) shows an altered (YIDD-to-CIDD) motif in the reverse transcriptase domain. HERV-K(C19) is truncated in the 5′ LTR and harbors a defective protease gene due to a point mutation. Direct amplification of proviral structures from single chromosomes by using chromosomal flanking primers was performed by long PCR for HERV-K(C7) and HERV-K(C19) and for type 1 proviruses HERV-K10 and HERV-K18 from chromosomes 5 and 1, respectively. HERV-K18, in contrast to HERV-K10, bears no intact gag ORF and shows close homology to HERV-K/IDDMK(1,2)22. In transfection experiments, HERV-K(C7) and HERV-K cDNA-based expression vectors yielded the proteins Gag and cORF whereas HERV-K10 vectors yielded Gag alone. The data suggest that the human genome does not contain an entire, intact proviral copy of HERV-K.